TLR4 Receptor D299G/T399I Haplotype Polymorphism Is Associated with Insulin Resistance in Obese Female Subjects - Sharif, Elham (Genes (Basel), 2020)
Background: Activation of Toll-like-receptor 4 (TLR4) causes chronic inflammation that can result in obesity and metabolic syndrome (MeS). Aim: This study aimed to investigate the role of TLR4 polymorphisms of TLR4D299G/T399I, and its impact on protein expression of TLR4 in obese female subjects. Methodology: A prospective cross-sectional association study was performed on Arab female subjects from Qatar University. The subjects were categorized according to BMI classifications into two groups: “obese; n = 69” and “non-obese; n = 136”. Anthropometric measurements, weight (kg), height (m) and waist circumference (WC) were evaluated, and the body mass index (BMI) was calculated. Fasting blood samples were collected, and assessment of glucose, lipid profile, C-reactive protein (CRP), leptin, IL-6 and insulin was performed. Insulin resistance was computed using HOMA-IR. Genotyping of the TLR4 polymorphisms of TLR4D299G (rs4986790) and TLR4T399I (rs4986791) was performed by the 5′ nuclease assay by TaqMan MGB probe. Flow cytometry was used to evaluate the monocyte cell surface expression of TLR4. Results: The frequency distribution of the genotype revealed that homozygous AA is the most frequent among obese subjects (86.4%) for (TLR4D299G, A > G) and the homozygous CC genotype is the most frequent (92.4%) for (TLR4T399I, C > T). Haplotype analysis of TLR4 D299G/T399I showed that GT carriers had a significant association with increased probability of insulin resistance (odds ratio = 4.73; 95% CI 1.19–18.90; p-value = 0.016). The monocyte cell surface of TLR4 was significantly higher by 1.3 folds in obese compared to non-obese subjects. Conclusions: TLR4 D299G/T399I haplotype polymorphism is associated with an increased risk of insulin resistance with the upregulation of TLR4 protein expression in obese subjects.